Exploring the Mechanisms of the Antioxidants BHA, BHT, and TBHQ in Hepatotoxicity, Nephrotoxicity, and Neurotoxicity from the Perspective of Network Toxicology - Jing Ren; Ziang Li; Xiaofen Li; Lin Yang; Zhulin Bu; Yuhui Wu; Yuting Li; Shuosheng Zhang; Xianglong Meng (Foods)
The widespread use of food additives, such as butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT), and tert-butylhydroquinone (TBHQ), has raised concerns about their potential toxicity, especially their hepatotoxicity, nephrotoxicity, and neurotoxicity. This study explores the targets and mechanisms of food additive-induced toxicity using network toxicology. Toxicity predictions of BHA, BHT, and TBHQ were performed using the ProTox-3.0, ADMETlab 3.0, and Xundrug databases, and potential targets were identified using the SwissTargetPrediction, Batman-TCM, SuperPred, and SEA databases. These were integrated with GeneCards—The Human Gene Database (GeneCards) and the Online Mendelian Inheritance in Man (OMIM) database to extract toxicity-related targets for subsequent Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. Core-acting genes were further screened through protein–protein interactions (PPIs), and molecular docking was performed to verify the binding free energy between BHA, BHT, and TBHQ and their core targets. Additionally, the mRNA-miRNA-lnRNA interaction regulatory networks of the core targets and potential carcinogenic mechanisms were analyzed. The targets of BHA, BHT, and TBHQ were as follows: ACE, HIF1A, NR1H4, NFKB1, TNF, IL6, IFNG, IL1B, and ESR1 for hepatotoxicity; APP, NFKB1, ACE, FOS, IL10, IL1B, IL6, TNF, and ALB for nephrotoxicity; and GRIN2B, IL1B, and TNF for neurotoxicity. These interactions primarily involved pathways such as interleukin-17 (IL-17) and Janus kinase-signal transducer and activator of transcription (JAK-STAT), as well as various pathways related to non-alcoholic fatty liver disease (NAFLD). This study highlights the potential toxicity of BHA, BHT, and TBHQ to the liver, kidneys, and nerves, providing insights for better safety evaluations.